2014
DOI: 10.1177/1098612x14550171
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility in bacterial isolates from Norwegian cats with lower urinary tract disease

Abstract: Studies of feline lower urinary tract disease (FLUTD) among Norwegian cats have shown higher prevalences of bacterial cystitis than most previously published reports. The aims of the present study were to identify bacterial isolates obtained from the urine of Norwegian cats with FLUTD and their susceptibility to antimicrobial agents. Eighty-two bacterial isolates from 72 urine cultures obtained from 71 different cats were included. Escherichia coli, Staphylococcus species, Enterococcus species and Streptococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
6
15
3
1
Order By: Relevance
“…Ampicillin, which has cross‐resistance to amoxicillin, the second recommended agent, 14 had a low IF of only 67.2. This is consistent with a recent study from Norway, which documented a low sensitivity of 58 per cent of urinary isolates to amoxicillin 47 . A current study from human medicine identified ampicillin as the least effective antimicrobial with 90 per cent resistance in UTIs 48 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ampicillin, which has cross‐resistance to amoxicillin, the second recommended agent, 14 had a low IF of only 67.2. This is consistent with a recent study from Norway, which documented a low sensitivity of 58 per cent of urinary isolates to amoxicillin 47 . A current study from human medicine identified ampicillin as the least effective antimicrobial with 90 per cent resistance in UTIs 48 .…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with a recent study from Norway, which documented a low sensitivity of 58 per cent of urinary isolates to amoxicillin. 47 A current study from human medicine identiied ampicillin as the least efective antimicrobial with 90 per cent resistance in UTIs. 48 Based on the results of these studies, amoxicillin cannot be recommended for empirical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other frequently documented microorganisms are Streptococcus species (2-19%), Enterococcus faecalis (5-27%) and Staphylococcus felis (17-20%). [6][7][8]34,35,44,63 E faecalis was more likely to be present in cats with subclinical bacteriuria (23%) than in cats with UTIs (11%). 29,34 Enterococcus species were previously considered commensal organisms of the gut flora with little clinical significance.…”
Section: Pathogensmentioning
confidence: 99%
“…In response to the concerns brought forward by Mark Papich related to the use of antibiotic susceptibility testing reported in the study published in JFMS , 1 we would like to offer the following comments.…”
mentioning
confidence: 99%